GOODS INVENTORY APPLICATION SYSTEM of "MEKAR JAYA" VILLAGE-OWNED ENTERPRISES (BUMDes) - Ari Bowo; Maharani Panggestu; Muhamad Muslihudin (IJISCS (International Journal of Information System and Computer Science), 2022)
Village-Owned Enterprises are known to the public as BUMDes according to Government Regulation Number 4 of 2015 concerning the Establishment, Management, and Management of Village-Owned Enterprises to manage assets, services, and other businesses for the welfare of the village community. BUMDes is one of the agencies working in the economic and social fields as a provider of agents to the community, especially in the village business sector. The problem in this study is that the recording of goods sold often results in errors in the details of the number of goods sold and the stock of goods that are still available at BUMDes Mekar Jaya. As a result, it interferes with the business marketing process because the available goods data is less accurate. The research method used in this research is data collection method, information system development method of System Development Life Cycle (SDLC), and fishbone diagram research flow. The analysis result of this study is that the web-based inventory application system at BUMDes Mekar Jaya in Panjerejo Village, Gadingrejo District, Pringsewu Regency has explained that by making a web-based inventory application system at BUMDes Mekar Jaya can improve work performance more, precisely and accurately. So, it can make it easier to work on reports of incoming goods or outgoing goods. For the manufacture of the application system, the researcher uses the PHP programming language and the MySQL database which is supported by several related applications. In this study, researchers also conducted testing using black box testing. A black box is a way to perform tests such as the functions which exist in the application to make it easier for general users. With the application system, this inventory can be used simultaneously with the old system so that within a certain time the old system can be abandoned and the new system can be fully used effectively.